Introducing Market Access Using Trade Map to Export Products for a Micro and Small Entrepreneur in Bandung - Angela, Francesca Klarensia; Rifawan, Affabile (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Rahsa Nusantara is an Indonesian start-up established in 2016 with a specialization in crafting natural products derived from local ingredients. One of their products is Sukhaloka, a natural collagen booster extracted from taro's tuber. This product is rich in hyaluronic acid, offering hair, skin, and nail’s health benefits. As Rahsa Nusantara aims to expand globally, the company faces challenges in gaining international market access. In response, a community empowerment program was conducted by Universitas Padjadjaran, collaborating with the Free Trade Agreement (FTA) Center. The program involved two weeks of preparation, foreign market research, and a virtual consultation session with FTA Center expert. The findings highlighted the potential export destinations, such as Japan, where the demand for collagen products is notably high. The FTA Center expert provided valuable insights and recommendations, including product positioning, cost breakdown, and the importance of certifications for specific markets. The program successfully equipped Rahsa Nusantara with knowledge and tools for effective market entry. The study concludes by emphasizing the need for ongoing collaboration, continuous market research, and the implementation of expert advice for sustained success in international trade.